A Study of Project Management Practices in the Czech Republic - Majra Hodžić; Helena Hrůzová (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The importance of project management has hastily increased and its rapid development and tendency towards innovation has made it one of the key components of organizations’ performance. Therefore, the main purpose of this paper was to conduct a systematic study of the current situation and practices in the field of project management in the Czech Republic. Four areas of project management are closely studied: stakeholders´ main demands and requests, main characteristics of project management, level of use of project management methods and identification of the characteristics of the respondents. The research has an explanatory character and works with primary and secondary data. Primary data was obtained through an on-line cross-sectional survey comprising of four parts (identical to the areas studied) conducted in the Czech Republic in 2016. The questionnaire consisted of twenty questions in total and it had elements of both quantitative and qualitative research. It yielded 118 usable responses. The sample examined was random but expert - it covered organizations operating in the Czech Republic and respondents were asked to identify their professionalism and experience in the area of project management. Furthermore, the results of the authors’ survey were compared with the results of similar surveys from the last five years providing secondary data. This comparison brought forth additional insights and better understanding of the theoretical grounding. The results showed a prominent relationship and, to some extent, a correlation between understanding (defining) a successful project and identifying success factors, stakeholder demands and problematic areas, displaying a complexity of working in the field of project management. Furthermore, a vaguely-defined scope was identified as the most problematic area and issue influencing project success. Overall, the study indicates the necessity for innovation, such as the development of a basic framework for project governance approaches as well as an increase in the use of available project management methods. These directions will not only improve project management, but will also boost entrepreneurship spirit and help modern, highly potential start-ups to be competitive in the market.